Design And Build Of Human Digestive System Interactive Learning Animation Based On Android For Class XI Students - irdham denni (Institut Pendidikan Indonesia, 2020)
Simulation-based educational games are designed to simulate existing problems in order to obtain the essence or knowledge that can be used to solve these problems. Today's rapid technological developments affect the learning process in elementary schools and also affect learning materials and the way in which material is delivered in the process of teaching and learning activities. At the educational stage of elementary school age children, students will tend to be more interested in games that are easy to play and in which there are bright colors and animated images that attract attention. The digestive system is a system that processes food and absorbs nutrients in the form of nutrients- nutrients needed by the body. The digestive system will also break down complex food molecules into simpler molecules with the help of enzymes so that they are easily digested by the body. This additional digestive organ serves to assist the digestive tract in doing its work. The teeth and tongue are located in the oral cavity, the gallbladder and the digestive glands are connected to the digestive tract through a channel. Additional digestive glands will produce secretions that contribute to the breakdown of foodstuffs. Teeth, tongue, gall bladder, some digestive glands such as salivary glands, liver and pancreas. Adobe Flash or previously Adobe Flash is a multifunctional software. Apart from its initial function, which is to facilitate the creation of web animations, it turns out that Macromedia Flash is growing rapidly so that it can be used as an extraordinary multi-media software. Even Adobe Flash with its action script can be used as an easy and effective game maker program. This research is also proposed by the author as the author's final project and as one of the requirements for achieving a diploma. And the author also hopes that the children's educational games created can be useful for children in Indonesia of preschool age.